Making the most of being mentored : how to grow from a mentoring partnership - Shea, Gordon F. (Crisp Pub. Menlo ParkUS, 1999)
Defines mentoring; mentor and mentee; and explores the benefits of the mentoring arrangement. Emphasises the need for mentees to be proactive and identifies 7 skills which they need to develop, including: asking productive questions; using trust-building behaviours and internalizing the mentor's input. Advises on building, maintaining and when appropriate, terminating a mentoring relationship. Identifies techniques for maximising results and thereafter, contributing to organizational growth.